Preparation and characterization of La2-xSmxMo1.8Al0.2O8.7 as electrolyte for solid oxide fuel cells. Issue 1 (1st December 2022) - Tian, Changan; Shao, Lingbo; Chen, Chao; Liu, Yang; Wang, Cao; Zhu, Lejie
Abstract: Solid oxide fuel cells (SOFCs) have been regarded as promising eco-friendly power sources in recent years owing to their high energy conversion efficiency and fuel flexibility. La2 Mo2 O9 -based ceramics draw researchers' attention due to their good performance as electrolyte materials for SOFCs. In this study, the Sm and Al co-doped La2 Mo2 O9, La2-xSmxMo1.8 Al0.2 O8.7 (x=0.1, 0.2, 0.3 and 04, LSMAO), are successfully synthesized by the sol-gel method as electrolyte materials for SOFCs. The phase evolution, sintering, the microstructural and electrochemical performance of LSMAO were observed by TG-DSC, XRD, SEM, and impedance analyses, respectively. The results show that the highly phase-pure cubic LSMAO nanopowders can be obtained after calcining at 600 °C for 2 h. The as-synthesized LSMAO powders exhibited a better sintering activity. All these samples were found to have a relative density above 94.5% after sintering at 950 °C for 5 h. The electrical performance study shows that higher doping concentrations of Sm caused a decrease in ionic conductivity and an increase in activation energy. La1.9Sm0.1Mo1.8 Al0.2 O8.7 exhibited the highest oxide ionic conductivity (σ800 °C=0.033 S/cm) and lowest electrical activation energy (Ea=0.85 eV). This shows that LSMAO could be used as a potential electrolyte for intermediate temperature SOFCs (IT-SOFCs).